KONDISI KELUARGA DAN PEMBELAJARAN BERWAWASAN GENDER PADA SISWA SEKOLAH DASAR - Herien Puspitawati (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2011)
Abstract:  The purpose of this cross-sectional research design was to describe teaching outlines the class with gender perspectives in the elementary school. The location of the research was in the Bogor City with three reputable elementary schools as sample as recommended by Education cunDepartment Bogor City.  Secunder data acquired from competence scholarship research 2010 that most of respondents came from the middle upper families with high educated father and mother. It was found that learning process at school was applied in good gender perspectives' ways for both male and female students, especially at a ‘prime' elementary school there was a little indication of gender bias of teacher's behaviors. However toward students, especially teachers were more likely to punish male students more often than female students and communicate softer to female than male students.   Abstrak: Penelitian dengan disain cross-sectional ini bertujuan untuk mengetahui garis besar pembelajaran di kelas berwawasan gender di sekolah dasar. Lokasi penelitian di Kota Bogor dengan sampel tiga SD yang mempunyai reputasi baik berdasarkan rekomendasi Dinas Pendidikan Kota Bogor. Data sekunder diambil dari penelitian Hibah Kompetensi 2010. Hasil penelitian menunjukkan sebagian besar konsumen berasal dari keluarga menengah ke atas dengan ayah dan ibu yang berpendidikan tinggi. Hasil penelitian juga menunjukkan bahwa proses pembelajaran di sekolah diterapkan dalam cara-cara berperspektif gender untuk siswa laki-laki dan perempuan, khususnya pada sekolah dasar yang "fondasi", terdapat indikasi yang terbatas adanya bias gender pada perilaku guru. Namun, guru lebih cenderung untuk menghukum  siswa laki-laki ketimbang siswa perempuan dan berkomunikasi lebih halus kepada siswa perempuan ketimbang siswa laki-laki.